РЕГУЛИРОВАНИЕ РАЗВИТИЯ ПИЩЕВОЙ ОТРАСЛИ В УСЛОВИЯХ СОВРЕМЕННОГО КАЗАХСТАНА (Journal of Economic Research & Business Administration, 2015)
The Main elements of the mechanism of the operation and regulations of the development APK in condition modern Kazakhstan must be founded on combination economic mechanism regulations with market mechanism, aswhich emerge: government regulation of the economy; the mechanism of the prices; financial-credit mechanism; the tax system; economic and commercial payment; the organization production, labour and management on enterprise APK; rural marketing.